Formation of Novel Food Supplement by using Medhya Rasayana Dravya - Fernando, T.D.B.; Herapathdeniya, S.K.M.K.; Nallaperuma, D.M. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Medhya rasayana is a vital concept in Ayurveda, focusing on promoting Dhee, Dhrthi and Smrthi by playing a crucial role in holistic health and wellbeing. Objective of this study is to develop and analysis of a novel food formula by using selected Medhya_rasayana materials. In this study, the final product subjected to physicochemical, phytochemical and chromatographic analysis. Due to availability and commonly usage, Brahmi (Bacopa monneiri Linn.), Mandukaparni (Centella asiatica Linn.) and Yashtimadhu (Glycyrrhiza glabra Linn.) were selected as Medhya rasayana materials for this novel food. Dried powders of these plants, oats, wheat, milk and cocoa powders were taken as main ingredients and prepared it as a cereal. Cocoa can boost mood and improve brain functions. But in here it used for gaining pleasant flavour because our main targeted group is young population. Otherwise, there is no any interaction between cocoa and these herbs. Organoleptic parameters of the final product were; brown color, sweet taste, pleasant odour and soft in texture. pH was 7.0. Hardness was 63N. Percentages of total ash value, water soluble ash value and moisture content were 1.2%, 0.15% and 6.3% respectively. Final product gave the results of Flavonoids, Phenols, Alkaloids. HPTLC fingerprint (Chloroform, nbutanol, toluene 1:1:1) gave four different peaks. Previous research studies shows that Flavanoids, Phenols, Alkaloids and Steroids are effective in brain tonic action. In detail nutritional analysis and standardization are essential for further studies.
Keywords: Food supplement; Brahmi; Mandukaparni; Yashtimadhu